Effects of different glass fibers on the transverse strength and elastic modulus of repairing acrylic resin - Derya Ozdemir Dogan; Esma Gul; Nilufer Polat; Sedef Topçuoğlu (Cumhuriyet University, 2013)
Objectives: The aim of this study was to evaluate the transverse strength and the elastic modulus of a heat-polymerized denture base resin repaired by adding various glass fibers into  an autopolymerizing acrylic resin. Background: The key problems frequently encountered in dentures are fractures. A durable repairing system for a denture base fracture is desired to avoid recurrent fracturing. Materials and Methods: Fifty rectangular (65 mm × 10 mm × 2.5 mm) heat polymerized resin specimens were prepared which were divided in to five groups, with each including ten specimens. For the repairing procedure, samples with the autopolymerizing resin reinforced with stick, woven and chopped glass fibers were prepared. In addition, control samples with the autopolymerizing resin alone (in the absence of the glass fibres) were also obtained. Three-point bending tests were performed on all specimens. Results: The mean transverse strength for the control samples was 78.93 MPa. The specimens repaired with stick fiber reinforced resin exhibited the highest mean transverse strength of 83.16 MPa. The mean elastic modulus of the control specimens was 2121.86 MPa. The mean elastic modulus of the stick group was 7420 MPa. The elastic modulus values of the stick fiber reinforced specimens were significantly higher than the other groups (p<0.05). Conclusions: Amongst all samples, the transverse strength and elastic modulus of the stick fiber reinforced samples was found to be the highest.